Dynamic and Reversible Aggregation of the Human CAP Superfamily Member GAPR-1 in Protein Inclusions in Saccharomyces cerevisiae. Issue 19 (17th September 2021) - Sirati, Nafiseh; Popova, Blagovesta; Molenaar, Martijn R.; Verhoek, Iris C.; Braus, Gerhard H.; Kaloyanova, Dora V.; Helms, J. Bernd
Graphical abstract: Highlights: GAPR-1-GFP expression in yeast results in the formation of protein inclusions. Inclusions formed by GAPR-1-GFP are dynamic and reversible structures. N-myristoylation and Zinc-binding regulate GAPR-1 inclusion formation. Similar factors control inclusion formation and amyloid-like aggregation in vitro. Abstract: Many proteins that can assemble into higher order structures termed amyloids can also concentrate into cytoplasmic inclusions via liquid–liquid phase separation. Here, we study the assembly of human Golgi-Associated plant Pathogenesis Related protein 1 (GAPR-1), an amyloidogenic protein of the Cysteine-rich secretory proteins, Antigen 5, and Pathogenesis-related 1 proteins (CAP) protein superfamily, into cytosolic inclusions in Saccharomyces cerevisiae . Overexpression of GAPR-1-GFP results in the formation GAPR-1 oligomers and fluorescent inclusions in yeast cytosol. These cytosolic inclusions are dynamic and reversible organelles that gradually increase during time of overexpression and decrease after promoter shut-off. Inclusion formation is, however, a regulated process that is influenced by factors other than protein expression levels. We identified N-myristoylation of GAPR-1 as an important determinant at early stages of inclusion formation. In addition, mutations in the conserved metal-binding site (His54 and His103) enhanced inclusion formation, suggesting that these residues prevent uncontrolled protein sequestration. In agreement with this, we find that addition of Zn 2+ metal ions enhances inclusion formation. Furthermore, Zn 2+ reduces GAPR-1 protein degradation, which indicates stabilization of GAPR-1 in inclusions. We propose that the properties underlying both the amyloidogenic properties and the reversible sequestration of GAPR-1 into inclusions play a role in the biological function of GAPR-1 and other CAP family members.